SIMILITUDE OF THE SEISMIC PROCESS - Sadovskiy M.A. (My University, 1987)
Assuming that the earthquake focus is a rock volume filled with aftershocks, the author considers the concept of the center C of an earthquake and the distance ri from it to any point on the earth's surface. For this purpose the volume occupied by aftershocks is replaced by a sphere of equal volume, i.e., by a spherical focus whose center will be assumed to be the earthquake center. Thus instead of having to deal with nominal and difficult to define zones of different earthquake intensities, the seismic hazard at a given site may be evaluated in terms of the earthquake energy and distance from the center of the earthquake. This is demonstrated by directly relating the distances measured in this way to the earthquake intensity.